Comparative price analysis of biological medicines: disparities generated by different pricing policies - Pontes, Marcela Amaral; Ribeiro, Alane Andrelino; Albuquerque, Flávia Caixeta; Leite Cotenzini, Silvana Nair (Frontiers in Pharmacology, 2024)
Introduction: biological medicines have been assuming an important role among the therapeutic options for several diseases, however, due to their complex production process, the products obtained from this technology have a high added value and do not reach the purchasing power of most patients, which overwhelms the budget of health systems. With the development of biosimilars, which have reduced production costs, it is expected that access to biological medicines will become broader. However, in Brazil, the criteria for determining the price of biosimilars, unlike the generic policy in the country, do not foresee a price reduction due to the reduction of development costs. Objective: to understand the impact of the current model of economic regulation on the availability and access of these products in the country, based on a comparative analysis in selected countries, and identify trends that can help to expand the availability and access to biological medicines. Method: quantitative and qualitative study, to identify the variation between the entry prices of biological medicines in Brazil and in selected countries, as well as the differences in the economic regulation policies established in these countries. Results: the results demonstrate that the current pricing model in Brazil has generated distortions in the prices of biosimilars in the market, which, consequently, makes it difficult for the population to access this category of products, in addition to allowing unsustainable market practices for the systems of public and private health in Brazil. It was also found that most of the analyzed countries, unlike Brazil, seek to harmonize the prices of different brands of the same molecule marketed in the country and with the international market, in addition to establishing incentive policies for indication and replacement by biosimilars, which expands the participation of biosimilars in the market significantly. Conclusion: based on the data presented, it is concluded that it is essential to build a broader political and regulatory debate on the market for biologicals and biosimilars in the country to guarantee the access of the Brazilian population to more cost-effective technologies, generate more competitive market and consequently contribute to the financial sustainability of health systems.